Capabilities and marginalised communities: The case of the indigenous ethnic minority traveller community and housing in Ireland - Dermot Coates; Paul Anand; Michelle Norris (The Open University, Economics Department, 2015)
The Pavee people (or Irish Traveller community) is a small, indigenous ethnic minority group and has been a part of Irish society for many centuries. This community holds to its own values, language, traditions and customs as part of a distinctive lifestyle and culture but they are widely regarded as one of the most marginalised and disadvantaged groups in Irish society. The experience of racism and discrimination is common to Irish Travellers, the Roma/Gypsy and other nomadic peoples and a number of international bodies have drawn explicit links between these groups. The authors utilise the capabilities approach as a multidimensional framework for analysing capability deprivation amongst Irish Travellers and as a tool for evaluating the success of public policy towards the community. Specifically, we emphasize the importance of a cluster of key themes including Traveller values, autonomy, self-sufficiency and choice and we explore the manner in which the housing experience of Irish Travellers contributes to capability deprivation amongst this community. We conclude that this goes beyond poor housing quality alone. This is also expressed through culturally-inappropriate service provision and the denial of opportunities to exercise choice and control over their own housing in addition to other spillover effects which can negatively impinge upon the freedom of this community to enjoy a life that they have reason to value. The paper concludes with a consideration of the usefulness of a consultative process to enable Irish Travellers to define their own list of capabilities and priorities with regard to housing and offers a Tool Kit to develop improved accommodation consultations as a potential resource for all stakeholders.
Keywords: 330; Travellers; housing; quality of life; capabilities approach; agency; choice